Enhancement of the immunity and body weight gain in broiler by feeding with the brewer’s yeast β-glucan degraded by gamma Co-60 radiation - Le , Quang Luan; Nguyen , Thanh Long (Nuclear Science and Technology, 2015)
The insoluble β-glucan extracted from the cell wall of brewer’s yeast was dispersed in deionized water for swelling, then irradiated in order to degrade into water-soluble β-glucan. The results revealed that the water-soluble β-glucan contents in the irradiated samples were increased with radiation dose to 25.89, 49.07 and 66.71%; whereas their molecular weight (Mw) decreased to 48.1, 23.0 and 10.8 kDa by gamma irradiation at 100, 200 and 300 kGy, respectively. The supplementation of poultry feed with the radiation degraded β-glucan enhanced both non-specific (total white blood cells, lymphocytes, neutrocytes) and specific immune components (anti-Newcastle disease, anti-Gumboro disease virus and anti-infectious bronchitis virus antibodies) in the broilers. In comparison with the control, broiler fed normal poultry foodstuff without β-glucan, the supplementation of radiation degraded β-glucan not only increased the survival rate of the testing broiler about 33.3% and their average body weight of about 24.4%, but also reduced the feed conversion rate from 4.8 to 3.1 kg. The β-glucan oligosaccharides that having Mw of about 25 kDa produced by gamma irradiation at 200 kGy showed the highest effect on the growth performance and immunomodulatory capability in the immune system of the testing broilers. This product is promising to be applied for production of the safe stimulator of immunity for broiler chickens.